Épisodes biographiques d'une élève dyslexique relatifs à la résolution d'un problème mathématique - Teresa Assude; Jeannette Tambone (Nantes Université, 2016)
What are the favourable conditions for mathematical learning specially in solving mathematical problems? To investigate this question, we identified episodes of a dyslexic student's biography that show the importance in mathematics learning of the way the didactical environment is organized. We highlight the way this student in spite of her disabilities is able to fulfil the pupil's position.